(untitled)
We use worker-firm matched data from Homebase to construct new real-time estimates of the impact of the COVID-19 pandemic on employment and hours worked of small businesses. We find four key results: (1) employment of small businesses in four of the hardest hit service sectors contracted by an estimated 17.8 million between mid-February and mid-April a staggering 60% decline with more than half of the decline due to business closures; (2) small business employment recovered by about 8.5 million between mid-April and mid-June and more than half of the closed businesses have reopenend, but since mid-June this recovery has stalled; (3) small businesses have rehired a large share of previously furloughed workers but their employment remains 20-30% below pre-pandemic levels; (4) average weekly hours of job stayers declined sharply in the second half of March but have since fully recovered. The estimates highlight the key role that small business closures and reopenings play not only for the dramatic decline in service sector employment but also for the recovery that has come to a halt in mid-June. Unless many of the still closed businesses reopen and rehiring picks up again, service sector employment will remain persistently lower., address = Montréal, author = André Kurmann and Étienne Lalé and Lien Ta, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = 330; Coronavirus; Beschäftigungseffekt; KMU; Schätzung, language = eng, number = 2020-09, publisher = Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, title = The impact of COVID-19 on small business employment and hours: Real-time estimates with homebase data, type = Document de travail, url = https://hdl.handle.net/10419/234809, year = 2020